2018
DOI: 10.3390/cryst8030140
|View full text |Cite
|
Sign up to set email alerts
|

The Jahn-Teller Distortion at High Pressure: The Case of Copper Difluoride

Abstract: The opposing effects of high pressure (in the GPa range) and the Jahn-Teller distortion led to many intriguing phenomena which are still not well understood. Here we report a combined experimental-theoretical study on the high-pressure behavior of an archetypical Jahn-Teller system, copper difluoride (CuF 2). At ambient conditions this compound adopts a distorted rutile structure of P2 1 /c symmetry. Raman scattering measurements performed up to 29 GPa indicate that CuF 2 undergoes a phase transition at 9 GPa.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 60 publications
5
28
0
Order By: Relevance
“…And since they tend to collapse fast under even moderate pressures, it could be that other polymorphic forms, such as the ribbon one, would become competitive at rather low pressures, even preceding the transformation to the layered form. The previously documented pressure-induced transformations of CuF 2 [47] and AgF 2 [11] as well as a large body of data for transition metal difluorides and dichlorides (see also [48] and references therein) seem to suggest this scenario as a viable one.…”
Section: Impact Of Temperature and Pressure On Stability And Polymorpmentioning
confidence: 91%
See 1 more Smart Citation
“…And since they tend to collapse fast under even moderate pressures, it could be that other polymorphic forms, such as the ribbon one, would become competitive at rather low pressures, even preceding the transformation to the layered form. The previously documented pressure-induced transformations of CuF 2 [47] and AgF 2 [11] as well as a large body of data for transition metal difluorides and dichlorides (see also [48] and references therein) seem to suggest this scenario as a viable one.…”
Section: Impact Of Temperature and Pressure On Stability And Polymorpmentioning
confidence: 91%
“…The common tangent method [17,46] allows for a rather crude estimate for the formation pressure of AgCl 2 of 35 GPa (at T → 0 K), and likely even higher pressures at elevated temperature. The more precise estimate requires calculations in the function of pressure to be performed, also including the ribbon polymorph, which should exhibit substantial compressibility, and several viable high-pressure polymorphs [11,47,48]. Moreover, while drawing the computed volume-based conclusions one should always remember that despite great performance of HSE06 functional for describing crystal and electronic structure of solids, the reproduction of van der Waals interactions is still imperfect.…”
Section: Impact Of Temperature and Pressure On Stability And Polymorpmentioning
confidence: 99%
“…2a). Persistence of the broad band gap is typical of undoped d 9 systems, 21,[29][30][31][32] and it points out to the robustness of the localized AFM interactions. These interactions which lead to insulating behaviour tend to act opposite to the band broadening which is usually seen at elevated pressure and consequently the band gap closing becomes much more difficult than for the diamagnetic semiconductors.…”
mentioning
confidence: 99%
“…Numerous experimental and theoretical investigations were conducted in order to establish the phase sequence for these compounds. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] The motivation for these studies was the fact that the behaviour of difluorides at these conditions can serve as an analogue of the high-pressure transformations of dioxides, in particular SiO2. 7,8 Moreover high-pressure studies on MF2 systems revealed a surprisingly wide range of structures adopted by these compounds.…”
Section: Introductionmentioning
confidence: 99%